Enasidenib: First Mutant IDH2 Inhibitor for the Treatment of Refractory and Relapsed Acute Myeloid Leukemia - Dogra, Raghav; Bhatia, Rohit; Shankar, Ravi; Bansal, Parveen; Rawal, Ravindra K. (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Acute myeloid leukemia is the collective name for different types of leukemias of myeloid origin affecting blood and bone marrow. The overproduction of immature myeloblasts (white blood cells) is the characteristic feature of AML, thus flooding the bone marrow and reducing its capacity to produce normal blood cells. USFDA on August 1, 2017, approved a drug named Enasidenib formerly known as AG-221 which is being marketed under the name Idhifa to treat R/R AML with IDH2 mutation. The present review depicts the broad profile of enasidenib including various aspects of chemistry, preclinical, clinical studies, pharmacokinetics, mode of action and toxicity studies. Methods: Various reports and research articles have been referred to summarize different aspects related to chemistry and pharmacokinetics of enasidenib. Clinical data was collected from various recently published clinical reports including clinical trial outcomes. Result: The various findings of enasidenib revealed that it has been designed to allosterically inhibit mutated IDH2 to treat R/R AML patients. It has also presented good safety and efficacy profile along with 9.3 months overall survival rates of patients in which disease has relapsed. The drug is still under study either in combination or solely to treat hematological malignancies. Molecular modeling studies revealed that enasidenib binds to its target through hydrophobic interaction and hydrogen bonding inside the binding pocket. Enasidenib is found to be associated with certain adverse effects like elevated bilirubin level, diarrhea, differentiation syndrome, decreased potassium and calcium levels, etc. Conclusion: Enasidenib or AG-221was introduced by FDA as an anticancer agent which was developed as a first in class, a selective allosteric inhibitor of the tumor target i.e. IDH2 for Relapsed or Refractory AML. Phase 1/2 clinical trial of Enasidenib resulted in the overall survival rate of 40.3% with CR of 19.3%. Phase III trial on the Enasidenib is still under process along with another trial to test its potency against other cell lines. Edasidenib is associated with certain adverse effects, which can be reduced by investigators by designing its newer derivatives on the basis of SAR studies. Hence, it may come in the light as a potent lead entity for anticancer treatment in the coming years.
Keywords: Acute myeloid leukemia